ALTERNATIVE AND NON-OBJECTIVE MUSLIM MALAY WORLDVIEWS IN DINA ZAMAN’S “KING OF THE SEA”: THROUGH THE LENS OF MAGICAL REALISM - Ida Baizura Bahar; Nor Kamal Nor Hashim (Universitas Islam Sumatera Utara (UISU), 2018)
Literary reviews on King of the Sea (2012), a collection of nine short stories, by the Malaysian author Dina Zaman (b. 1969), have highlighted the theme of the supernatural through issues on the diversity of the Muslim Malay way of life. The text is a fictional narrative on the Muslim Malay beliefs and practices in the phenomenon of supernatural existence and how the influence of beliefs in the supernatural is inherent in the Malay culture. While literary critics agree that the stories are weaved with aspects of the magical to make it more culturally acceptable as a social reality, Bradley (2012: 206), however, contests this view by describing it as Dina’s transient and elusive attempt at magical realism although he concedes that there exist some vague impressions of it. Here, magical realism is understood to be fantastical elements which are miraculous, yet seen as ordinary, and ordinary as miraculous where the reality is not abandoned but is extended. Focussing on Dina’s depictions of supernatural beliefs among the Muslim Malay characters, this paper aims to discover how the alternative and non-objective Muslim Malay worldviews are demonstrated by the author in King of the Sea using the understanding of magical realism as conceptualised by Maggie Ann Bowers (2004). The findings show that Dina depicts the alternative and non-objective Muslim Malay worldviews of the Muslim Malay characters as grounded in their beliefs in the local Malay superstitions, myths and legends reflected through literary elements which are indeed characteristics of magical realism.